Eucalyptus scab and shoot malformation: A new and serious foliar disease of Eucalyptus caused by Elsinoe necatrix sp. nov. (17th February 2021) - Pham, Nam Q.; Marincowitz, Seonju; Solís, Myriam; Duong, Tuan A.; Wingfield, Brenda D.; Barnes, Irene; Slippers, Bernard; Muro Abad, Jupiter I.; Durán, Alvaro; Wingfield, Michael J.
Abstract: In 2014, a new and serious leaf and shoot disease of unknown aetiology appeared in Eucalyptus plantations of North Sumatra, Indonesia. The disease is characterized by black necrotic spots that initially appear on young leaves and petioles, which become scab‐like as the lesions age. Infected trees respond to infection by producing shoots with small leaves that commonly appear feathered. Fruiting structures typical of most foliar pathogens are not seen, but using scanning electron microscopy (SEM), fungal spores are evident and associated with the scab‐like structures. Using culture‐dependent methods, cultures resembling a species of Elsinoe were isolated from the lesions. DNA sequence comparisons for four gene regions, as well as morphological observations, showed that the fungus is an undescribed species in Elsinoe, for which the name Elsinoe necatrix sp. nov. is provided. Pathogenicity trials on a Eucalyptus clone with the Elsinoe species resulted in scab‐like structures similar to those observed under field conditions and the fungus was easily reisolated from the resulting lesions. This study includes a description of the pathogen and characterization of the disease, for which the name Eucalyptus scab and shoot malformation is suggested. Abstract : The causal agent of a new Eucalyptus disease of unknown aetiology was identified as a novel species in Elsinoe based on isolations from tissues with symptoms, multigene phylogenetic analyses, and pathogenicity trials.